1988
DOI: 10.1073/pnas.85.21.8171
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with BK virus may break immunological tolerance to histone and DNA antigens.

Abstract: BK virus particles contain histones ofhost cell origin that combine with viral DNA to form minichromosomes. Data from earlier immunoblotting experiments demonstrated that rabbits inoculated i.v. with purified infectious BK virus produced antibodies not only to the viral structural protein VP1 but also to migrating polypeptides of a molecular mass ranging from 14-16 kDa. These proteins were believed to represent certain histone classes. To examine this hypothesis, sera from five rabbits inoculated with BK virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1

Year Published

1994
1994
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
3
32
1
Order By: Relevance
“…Immune self-tolerance after immunization with purified intracellular self-antigens such as cytochrome c (21) and histones (22) is well established, though immunity to these molecules can be elicited under some circumstances (22)(23)(24). Our data confirm the lack of immune reactivity to purified histones in normal mice and highlight the incomplete nature of tolerance to the La and Ro polypeptides, which can initiate autoimmunity in their own right.…”
Section: Discussionsupporting
confidence: 74%
“…Immune self-tolerance after immunization with purified intracellular self-antigens such as cytochrome c (21) and histones (22) is well established, though immunity to these molecules can be elicited under some circumstances (22)(23)(24). Our data confirm the lack of immune reactivity to purified histones in normal mice and highlight the incomplete nature of tolerance to the La and Ro polypeptides, which can initiate autoimmunity in their own right.…”
Section: Discussionsupporting
confidence: 74%
“…This has also been indicated by using polyoma virus BK (BKV) or its genomic DNA for induction of such antibodies. Inoculation of animals with BKV has been shown to result in selective production of anti-dsDNA and anti-histone autoantibodies in both rabbits (4,5) and mice (6). The induced anti-DNA antibodies have recently been shown to be serologically and structurally similar to antidsDNA antibodies present in SLE (7).…”
mentioning
confidence: 99%
“…Although the origin of anti-dsDNA antibodies remains controversial (3), results from recent experiments have indicated that DNA itself may be an immunogen (4)(5)(6)(7)(8). This has also been indicated by using polyoma virus BK (BKV) or its genomic DNA for induction of such antibodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complexes of native bacterial DNA and mBSA (Gilkeson et al 1989) are immunogenic; however, the antibody induced with those complexes binds poorly if at all to mammalian nDNA. Likewise, the anti-DNA antibody induced by BK virus inoculation binds to dsDNA but has specificity for dsDNA that is different from the dsDNA specificity of antoimmune anti-DNA antibody (Flaegstad et al 1988;Fredriksen et al 1990Fredriksen et al , 1991.…”
Section: Dna Specificity and V Region Structuresmentioning
confidence: 99%